(untitled) (Jurnal Bina Praja, 2025)
This research aims to assess the level of community readiness in indigenous communities affected by the relocation to the new capital city. The concept of community readiness is an approach to evaluate how prepared a community is to address certain issues or implement changes. The research was conducted by using Delphi analysis with three experts to determine and validate the appropriate parameters and variables for assessing community readiness and its factors. The parameters and variables obtained are then used as input for the readiness analysis to derive values and their factors. Subsequently, strategies are developed using descriptive qualitative techniques based on existing conditions, best practices, and existing regulations in Indonesia. The research results yielded 28 community readiness parameters and 10 variables to determine the factors. These parameters were then tested with 200 respondents, resulting in a score of 3.06, equivalent to Level 5 or the Preparation Level, where the leaders have started planning with the support and efforts of the community.